Kyrill von Alexandrien – Contra Iulianum - Riedweg, Christoph (De Gruyter, 2015)
Die monumentale Widerlegung
10.1515/9783110362626
Keywords: Apologetics / Early works to 1800; Antike Philosophie; Critical Edition; Greek Philology and Philosophy; Heidentum; Kyrill von Alexandrien; Paganism/Early Christianity; Patristics; Patristik; RELIGION / Christian Theology / History